Kikuchi Necrotising Lymphadenitis in a Child: A Rare Case Report - Sachin Goel; Ankur Gupta; Kanwar Sen; Pooja Swami (Dubai Medical Journal, 2020)
Introduction: Kikuchi-Fujimoto disease (KFD) is a rare benign disease with a self-limiting course. Patients usually present with clinical features of tender cervical lymphadenopathy (LAP), fever, malaise, weight loss, and night sweats. The disease may mimic infective LAP or lymphoma on clinical and histopathological examination (HPE). Case Report: We report a case of 3-year-old male child who presented to us with bilateral cervical LAP not responding to conservative management. Excision biopsy was done and HPE revealed KFD. Conclusion: Clinicians should have high index of suspicion for diagnosis of KFD in patients with cervical LAP not responding to conservative management. Excision biopsy is important for accurate diagnosis and to avoid aggressive interventions like chemotherapy.